Museum scènes / Staging the Museum. - Liefooghe, Maarten; Çiçek, Asli; Engels, Jantje (Rotterdam : Stichting OASE, 2022)
Museums facilitate encounters among visitors, objects, and stories while also facilitating the staging of these visits. In the 19th century, the transition from city to museum interior was dramatized, while in the 20th-century post-war period the “barrier-free” museum emerged in an attempt to abolish this boundary. Today, other boundaries are being rethought as well, such as opening up depots and restoration studios to the public. This edition examines how historical and contemporary buildings stage museum visits and museum activities, how permanent furnishing and temporary scenography interact, and how museums display their activities either transparently or imaginatively.
boek